Role of navigational ability in website visit duration. (4th April 2019) - Bhatnagar, Amit; Sinha, Atish P.; Sen, Arun
Abstract : Purpose: Online search effort is routinely measured by the duration of visit at the website as obtained from clicksream data or surveys. Measuring search effort by the time spent at a website assumes that all consumers who search for the same duration obtain the same amount of information. This would be acceptable if all consumers possessed the same navigational ability. In practice, different consumers have different levels of ability to navigate a website. The purpose of this study is to find whether an individual's navigational ability has an influence on visit duration and purchase likelihood. Design/methodology/approach: The authors use visit duration data from a real website which makes it possible to partition the visit duration into the times spent on relevant and irrelevant pages. The data were collected through an experimental study. The authors develop an empirical model, comprising hazard and choice models, to assess the relationship between navigational ability and elements of website usage. Findings: A consumer with poor navigational ability spends more time searching on the Web and has lower purchase probability compared to a consumer with superior ability. Research limitations/implications: The study is limited to one data. Practical implications: This research has managerial implications for website design, such as link-structure, appearance, size and the number of graphics. Originality/value: This is the first study to research navigational ability's influence on online consumer behavior.